Capacity : create laser focus, boundless energy, and an unstoppable drive in any organization - Johnson, Chris, 1957-; Johnson, Matt, 1986- (John Wiley & Sons, 2018)
Optimize your talent by removing the obstacles in their path Capacity is a proven system for bringing the best out of your team-and yourself. Matt and Chris Johnson set the mark on how to succeed in the future with their energizing message, humorous stories and their generational differences. As the world speeds-up faster and faster, organizations and their people try to keep up. This pressure to do more with less has reached epidemic levels of concern and organizations are panicking on how to recruit, retain and attract the best talent for the future. Burnout, low engagement, and overwhelming stress are jeopardizing organizations' ability to scale and win. As outdated performance models of the past crumble under pressure, Matt and Chris show you how to build and protect your most valuable asset--YOUR PEOPLE. What if you could beat the clock and expand your capacity by 6 hours per week? Or 11? Think about the organizational impact if your workforce were given fresh capacity to perform, lead, and grow. This book offers a clear, workable solution for organizations functioning in the real world: by paring it down to three performance pillars they must have to succeed--focus, energy, and drive. Ever organization sets initiatives, but many remain unfinished because their capacity to do so fails before it starts. This framework is different: these changes bring the type of benefits that cause transformation. Giving your people what they need makes buy-in irrelevant, and allows them to perform at their highest potential. Not only can it work, but it is the only thing that will work over the long term. By making your organization a great place to work, you retain your best talent and attract more like it. With dedicated resources, focus, sustainable effort, and comprehensive strategy, your top performers will be equipped to drive your organization to the top. Among Capacity's Key Points: Learn what top performers need to produce their very best work Discover the biggest factor influencing your team's FOCUS, ENERGY and DRIVE Prevent burnout and stimulate innovation by allowing your people to have a bigger container Adopt a strategy of expanding capacity to exceed your high-performance goals Deeply personal, but organizational focused. Capacity is an engaging and even life changing book Capacity is the next big paradigm shift for the future of training and development --as we shift to the world of the knowledge worker, it is not information or talent that ...